Fuzzy Logic in Determining Hotel Priorities for The Halal Tourism Industry in Garut City - Ramdhani, Rizky Fajar; Romlah, Siti; Fanani, Ivan (Islamicate Institute, 2020)
Garut Regency is one of the 13 districts designated by the West Java Provincial Government as a halal tourist destination because the various tours that Garut Regency has, such as natural, cultural, special interest, and artificial tourism are very supportive of the development of halal tourism in Indonesia, especially Java. West. Moreover, the majority of Garut residents are Muslim (99.77%). Various selected facilities for sharia tourism, such as hotels, continue to be developed based on the Muslim friendly principle. However, the use of sharia in hotels in Garut as promoted by the Garut Tourism Office is a self-declaration until now, there are no hotels in Garut that already have a halal certificate. So that the problem points to be formulated and known in this study is the extent to which hotels in Garut, especially in the tourist area of ​​Cipanas, have fulfilled the Islamic concept based on Permen Paweka No. 2 of 2014 concerning